2010
DOI: 10.1016/j.cplett.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectrum of proflavine and its ions

Abstract: Motivated by possible astrophysical and biological applications we calculate visible and near UV spectral lines of proflavine (C 13 H 11 N 3 , 3,6-diaminoacridine) in vacuum, as well as its anion, cation, and dication. The pseudopotential density functional and time-dependent density functional methods are used. We find a good agreement in spectral line positions calculated by two real-time propagation methods and the Lanczos chain method. Spectra of proflavine and its ions show characteristic UV lines which a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
(92 reference statements)
1
14
0
Order By: Relevance
“…It is also noted that at a nominal ortho to para ratio of 3:1, the calculated spectrum of CH 2 CN − does not match the observed spectra. Similarly, a recent claim that proflavine and its anion, cation, and di-cation are responsible for the 4066 Å, 4363 Å, 4175 Å, and 5259 Å DIBs (Bonaca & Bilalbegović 2010) requires verification. The proposition is based on computed optical absorption wavelengths using pseudo-potential density functional theory methods.…”
Section: The Long and Eventful History Of Dib Candidatesmentioning
confidence: 99%
“…It is also noted that at a nominal ortho to para ratio of 3:1, the calculated spectrum of CH 2 CN − does not match the observed spectra. Similarly, a recent claim that proflavine and its anion, cation, and di-cation are responsible for the 4066 Å, 4363 Å, 4175 Å, and 5259 Å DIBs (Bonaca & Bilalbegović 2010) requires verification. The proposition is based on computed optical absorption wavelengths using pseudo-potential density functional theory methods.…”
Section: The Long and Eventful History Of Dib Candidatesmentioning
confidence: 99%
“…The near‐UV channel of COS shows a high sensitivity in the region between 200 and 300 nm where lines of hydrogenated protonated naphthalene and proflavine exist. The lines at 281 and 422 nm in the spectrum of the proflavine cation [Bonaca 2010] move to 273 and 454 nm, and three new lines appear between these two in the spectrum of H–C 13 H 11 N + 3 (position I). Rather strong lines exist at 201, 222 and 244 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the results of TDDFT calculations (within the Tamm–Dancoff approximation and using the Becke–Lee–Yang–Parr (BLYP) functional) for the excitation energies of several PAH cations agree with experiments to within 0.3 eV (Hirata et al 1999). We have found that calculations with the B3LYP functional (still in development in the latest version of the octopus code) do not change the spectrum of proflavine substantially (Bonaca & Bilalbegović 2010). It has also been found that spectra of proflavine obtained using the time‐propagation method in the octopus code agree with the results of the Lanczos‐chain TDDFT module in Quantum ESPRESSO (Walker et al 2006; Bonaca & Bilalbegović 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations